Use of Virtual Reality in Dentistry: Literature Review - Genaro, Luis Eduardo (2020)
Virtual reality (VR) allows its application in different fields, such as healthcare. In dentistry, this technology has enormous potential, in the educational and clinical scope. Its applications are of increasing interest and importance in dentistry, especially in teaching, as it offers interactivity and high effectiveness in learning. In the treatment of phobia to dental treatments, this technology is also promising, since it shows satisfactory results and in the surgical area it has a high potential for complex treatments, allowing predictable and safe results. However, future studies should focus on establishing technological standards with high data quality and on the development of approved applications for the clinical routine. Thus, the objective of this literature review was to provide clarification on the knowledge and scientific development of VR in dentistry.